Parallel route distributing model in reconfigurable cluster router - Wen-long CHEN; Ming-wei XU; Ke XU (Tongxin xuebao)
Long distribution delay and load unbalance of router cards were the key problems of traditional route distribution techniques.Especially,in reconfigurable cluster routers,the number of linecards significantly increased,which made the problem highlighted.To address this issue,the TPRD(tree-based parallel route distribution)model was proposed after systematically analyzing existing route distribution methods and the cluster router architecture.In TPRD,all cards of cluster router were constructed to an unbalanced distribution tree and routes were transferred form the root node to leaf nodes.The algorithms and deployment approaches for implementation of TPRD were presented.The NS2 simulation results demonstrated TPRD achieved an expected performance.